EXPLORATION OF INTERSEX STRUGGLE IN ARUNDHATI ROY’S THE MINISTRY OF UTMOST HAPPINESS - Suman, Avdhesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper aims to critically analyse the struggles of the intersex in Indian society referencing the novel of Arundhati Roy’s The Ministry of Utmost Happiness. In general, every society recognises only two polarities, or sexes, based on the genitalia at birth which are male and female through the process of sex assignment. But in another case when the genitalia do not confirm whether it is male or female it is called intersex. When a person’s internal reproductive system, external genitalia, and sex chromosomes do not correspond to a male or female, they are referred to as intersexual. Such intersexual persons do not belong to either gender, they are referred to as transgender or third gender. In India, the transgender community has endured centuries of social, political, and economic marginalisation and discrimination. They always keep away from the mainstream of society. The majority of transgenders face challenging upbringings and formidable obstacles in their adulthood. They frequently experience emotional and physical abuse, including sexual assault. They are abandoned and invisible in society because they do not fit into the established social norms, which leaves them with severe wounds, particularly to their identity. Despite facing hundreds of problems these people are creating new lives for themselves. Hence, this paper attempts to demonstrate their psychological and social struggles through the character of Anjum, a Hijra.